2008
DOI: 10.1080/00918360802265685
|View full text |Cite
|
Sign up to set email alerts
|

Gender Role Identity in a Sample of Italian Male Homosexuals

Abstract: Gender role is a multifactorial concept, as gender-related attitudes, behaviors, and personality are partially autonomous. The aim of the study was to evaluate the prevalent gender role identity in a sample of male homosexuals. One hundred male homosexuals and 50 male heterosexuals matched for age and sex, have been assessed with the Italian version of the Bem Sex-Role Inventory (BSRI; Bem, 1974). Statistically significant differences have been found between the two groups at the dimensions "Masculine" (z = 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This also showed that people's who placed these advertisements could negate their own feminine traits if they are present 31 . "Feminine features" are always possible in whomever men without taking into account their sexual orientation.…”
Section: Discussionmentioning
confidence: 96%
“…This also showed that people's who placed these advertisements could negate their own feminine traits if they are present 31 . "Feminine features" are always possible in whomever men without taking into account their sexual orientation.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous studies have shown that the BSRI has a predictive value for many gender-related qualities. The BSRI displayed lower masculinity scores in gay males (Zoccali et al, 2008), higher masculinity scores in women with physical traits that indicate higher levels of prenatal exposure to testosterone (Csathó et al, 2003), higher masculinity scores for women in risk-taking sports (Cazenave, Le Scanff, & Woodman, 2007), and higher femininity scores in gays and lesbians with eating disorders (Meyer, Blissett, & Oldfield, 2001). In a recent review on the usefulness of the BSRI, Oswald (2004) emphasized the measurement validity and established usefulness.…”
mentioning
confidence: 99%